Combined effects of spray‐drying conditions and postdrying storage time and temperature on Salmonella choleraesuis and Salmonella typhimurium survival when inoculated in liquid porcine plasma. (1st August 2018) - Blázquez, E.; Rodríguez, C.; Ródenas, J.; Saborido, N.; Solà‐Ginés, M.; Pérez de Rozas, A.; Campbell, J. M.; Segalés, J.; Pujols, J.; Polo, J.
Abstract: The objective of this study was to determine the effectiveness of the spray‐drying process on the inactivation of Salmonella choleraesuis and Salmonella typhimurium spiked in liquid porcine plasma and to test the additive effect of immediate postdrying storage. Commercial spray‐dried porcine plasma was sterilized by irradiation and then reconstituted (1:9) with sterile water. Aliquots of reconstituted plasma were inoculated with either S. choleraesuis or S. typhimurium, subjected to spray‐drying at an inlet temperature of 200°C and an outlet temperature of either 71 or 80°C, and each spray‐drying temperature combinations were subjected to either 0, 30 or 60 s of residence time (RT) as a simulation of residence time typical of commercial dryers. Spray‐dried samples were stored at either 4·0 ± 3·0°C or 23·0 ± 0·3°C for 15 days. Bacterial counts of each Salmonella spp., were completed for all samples. For both Salmonella spp., spray‐drying at both outlet temperatures reduced bacterial counts about 3 logs at RT 0 s, while there was about a 5·5 log reduction at RT 60 s. Storage of all dried samples at either 4·0 ± 3·0°C or 23·0 ± 0·3°C for 15 days eliminate all detectable bacterial counts of both Salmonella spp. Significance and Impact of the Study: Safety of raw materials from animal origin like spray‐dried porcine plasma (SDPP) may be a concern for the swine industry. Spray‐drying process and postdrying storage are good inactivation steps to reduce the bacterial load of Salmonella choleraesuis and Salmonella typhimurium . For both Salmonella spp., spray‐drying at 71°C or 80°C outlet temperatures reduced bacterial counts about 3 log at residence time (RT) 0 s, while there was about a 5.5 log reduction at RT 60 s. Storage of all dried samples at either 4.0 ± 3.0°C or 23.0 ± 0.3°C for 15 days was effective for eliminating detectable bacterial counts of both Salmonella spp.